Исследование процесса термического разложения мелкодисперсного карбонатного сырья и некоторых свойств продукта обжига - Питак, Инна Вячеславовна; Шапорев, Валерий Павлович; Васильев, Михаил Ильич (SPC PC "TECHNOLOGY CENTER", 2015)
В данной работе рассмотрены вопросы обжига мелкодисперсного карбонатного сырья. Приведены результаты комплексного исследования физико-химических свойств нескольких видов мелкодисперсного карбонатного сырья и закономерностей его термической диссоциации, которые позволили установить для каждого случая кинетические и технологические параметры процесса термической диссоциации сырья, при которых достигается максимальная степень превращения СаСО₃ в СаО, при этом продукт обладает наибольшей активностью.

The problems of the roasting of finely divided carbonate raw material are considered in the article. The aim of the research is to determine the physical and chemical laws, by which we can manage the process and roasting product quality. Some results of a comprehensive study of the physical and chemical properties of several kinds of finely divided carbonate raw materials and the laws of its thermal dissociation are given, physical and chemical properties of the dissociation products are defined. They are allowed to establish in each case the kinetic and technological parameters of thermal dissociation process of raw materials, at which the maximum conversion rate of CaCOм into CaO is observed, whereby the product has the highest activity. The practical application of the principle of the results will reduce investment in the creation of the unit, improve the furnace performance for the final product. This process organization on the basis of the research results provides the optimal regimes of carbonate waste preparation and their firing to obtain highly active lime and production effectiveness.
Investigation of thermal decomposition process of finely divided carbonate raw materials and some properties of the roasting product
Keywords: состав гранулометрический; диссоциация; процесс технологический; отходы промышленные; roasting; carbonate raw materials; particle size distribution; thermal dissociation